Drones and their application in logistics - Boncsér, Levente; Cservenák, Ákos; Kröpfl, Patrick; Landschützer, Christian (Advanced Logistic Systems - Theory and Practice, 2024)
The widespread adoption and utilization of drones often raise questions regarding what exactly constitutes a drone and the characteristics that categorize a device into this category. In the first section, we attempt to define the concept of a drone, emphasizing its diversity and the misconceptions surrounding its terminology. The second section introduces classifications based on the main features of drones to better understand their application areas. The third and fourth sections examine daily and military uses, as well as the logistical role of drones, highlighting emerging challenges and limitations. Finally, we summarize the potential dangers of drone use, legal restrictions, as well as public opinion and cybersecurity concerns, which frequently hinder their broader adoption and application.